Analisis Perhitungan Harga Pokok Produksi Pada UMKM Dengan Menerapkan Metode Full Costing Dalam Menentukan Harga Jual (Studi Kasus Pada Usaha Tahu Bapak Suwardi) - Ahmad Fauzan; Andi Irfan (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to determine the determination of the cost of production at Mr Suwardi's Tofu Business before and after using the Full Costing method. The research method used is a descriptive method, namely a research method by collecting data that is appropriate to the actual situation, then the data is compiled, processed and analyzed to provide an overview of the existing problem. Primary data collection techniques were carried out by means of structured interviews and observations, secondary data collection techniques were carried out by means of literature study. The data analysis technique used in determining the cost of production is by applying the Full Costing method. Based on the research results, there are differences in HPP calculations before and after using the Full Costing method. So that the selling price is set higher than the selling price set by the company, because the higher the production costs incurred, the higher the selling price set.